Analisis Customer Rating dan Customer Review terhadap Keputusan Pembelian Produk Makanan Secara Online : Studi Kasus pada Konsumen Pengguna Jasa Pesan Antar Shopee Food di Kota Solo - Annisa Indah Mutiasari; Anggit Dyah Kusumastuti; Rusnandari Retno Cahyani; Firdhaus Hari Saputro Al Haris (Jurnal Simki Economic, 2024)
The development of technology that is increasingly advanced today has led to changes in consumer behavior in buying food. The phenomenon of food delivery services through applications has made it easier for people to buy food without having to leave home. The purpose of this research is to determine the influence of customer rating and customer review variables on the purchasing decisions of food products through the Shopee Food delivery service in Solo City, Central Java. Respondents in this study are buyers who have used the food delivery service through Shopee Food, totaling 100 people. The results of the study indicate that, partially, the customer rating variable does not influence the purchasing decision, while the customer review variable affects the purchasing decision. The most dominant variable influencing this study is the customer review variable.